Interest of Senior Secondary Students in Physics topics with Biological Science. - B. M., Manohara.; M S, RAMESHA; Lingaraju, (International Journal of Psychosocial Rehabilitation, 2019)
This project introduces the electricity concept from a senior secondary school physics class for biological along with health science learners. These pupils think that their future careers or professional lives are unrelated to physics. They believe that they cannot succeed in the subject unless they memorise several mathematical formulae and use them during the exam. By demonstrating the role of electricity in biological processes, we were able to demonstrate the connection between physics with biological and health sciences. The examples and situations provided in class have been found to affect how students' views. It can be quite difficult to tell if physics or biological sciences is the cause of a problem since the process of researching biological sciences in relation to physics is highly intricate. This is valid for all research techniques, including those that include observation, the identification of fresh scientific facts, measurement, and mistake correction. These issues are not included in conventional physics and biological science curriculum, despite their critical relevance.